Effect of Gloriosa superba and Catharanthus roseus Extracts on IFN-γ-Induced Keratin 17 Expression in HaCaT Human Keratinocytes. (10th November 2014) - Pattarachotanant, Nattaporn; Rakkhitawatthana, Varaporn; Tencomnao, Tewin
Abstract : Gloriosa superba and Catharanthus roseus are useful in traditional medicine for treatment of various skin diseases and cancer. However, their molecular effect on psoriasis has not been investigated. In this study, the effect of ethanol extracts derived from G. superba leaves and C. roseus stems on the expression of psoriatic marker, keratin 17 (K17), was investigated in human keratinocytes using biochemical and molecular experimental approaches. Both extracts could reduce the expression of K17 in a dose-dependent manner through JAK/STAT pathway as demonstrated by an observation of reduced phosphorylation of STAT3 (p-STAT3). The inhibitory activity of G. superba extract was more potent than that of C. roseus . The Pearson's correlation between K17 and cell viability was shown positive. Taken together, the extracts of G. superba and C. roseus may be developed as alternative therapies for psoriasis.